2011
DOI: 10.1177/0148607111414431
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of Parenteral Nutrition Volume Reduction, Without Weight Loss, After Stopping Teduglutide in a Subset of Patients With Short Bowel Syndrome

Abstract: Gastrointestinal anatomy, baseline BMI, and PN volume reduction on-drug predicted change in BMI off-drug. Whether this response would be maintained for a longer time or in the context of a challenging clinical situation has not been evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 17 publications
0
42
0
Order By: Relevance
“…Subjects with increased (INC) PN requirements by 12 months after stopping teduglutide 46 had a greater ( P = .04) PN volume reduction while on drug compared with those with stable (STABLE) or decreased (DEC) requirements at 12 months off drug (−4.7 vs −1.9 L/wk, respectively). INC had increased ( P < .001) PN requirements at 3, 6, and 12 months off drug vs study end while STABLE/DEC requirements did not change.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Subjects with increased (INC) PN requirements by 12 months after stopping teduglutide 46 had a greater ( P = .04) PN volume reduction while on drug compared with those with stable (STABLE) or decreased (DEC) requirements at 12 months off drug (−4.7 vs −1.9 L/wk, respectively). INC had increased ( P < .001) PN requirements at 3, 6, and 12 months off drug vs study end while STABLE/DEC requirements did not change.…”
Section: Resultsmentioning
confidence: 97%
“…High risk of allocation concealment (selection) and blinding of participants and personnel (performance) bias were noted in the open‐label Jeppesen et al, 42 , 43 Iyer et al, 44 and Fujioka et al 45 studies. Risk of blinding of outcome assessment (detection) bias was also high in the Gilroy et al, 38 Compher et al, 46 and Ukleja et al 47 studies since the treatments were known by the outcome assessors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our cohort, two patients had teduglutide therapy stopped after remaining completely off parenteral support for several months. Both had some part of their colon in place; this may be a positive predictor for stability off teduglutide once the parenteral support is weaned off [33]. …”
Section: Discussionmentioning
confidence: 99%
“…Phase III clinical trials have recently demonstrated that, in a randomized placebo-controlled trial, patients given teduglutide, a DPP-IV-resistant GLP-2 analog, had a statistically significant decrease in parenteral nutrition (PN) volume and in some cases were liberated from PN (21). In the near future, a GLP-2 analog will likely become available as an adjunct therapy for patients who suffer from intestinal failure (4,9,21,24,41).…”
mentioning
confidence: 99%